2004
DOI: 10.2170/jjphysiol.54.331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 20-Week Intermittent Cold-Water-Immersion on Phenotype and Myonuclei in Single Fibers of Rat Hindlimb Muscles

Abstract: fibers was less in cold-exposed group than controls (p < 0.05). The mean CSA and myonuclear number in type I MHC fibers of soleus muscle in cold-exposed group were significantly less than controls. Myonuclear domain in type IIa fibers of EDL in the cold-exposed group was greater than controls (p < 0.05). It is suggested that prolonged cold exposure causes the fibertype-specific adaptation in rat hindlimb muscles. It is further indicated that cold-exposure-related modulation of myonuclear number was closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…The percent distribution of fibers expressing type I, I ϩ IIa, or IIa MHC of the same soleus muscle as in the current study was identical for the control and cold-exposed groups [24]. However, a significant shift of the fiber phenotype expression from type IIb to IIa MHC was noted in EDL following cold exposure.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The percent distribution of fibers expressing type I, I ϩ IIa, or IIa MHC of the same soleus muscle as in the current study was identical for the control and cold-exposed groups [24]. However, a significant shift of the fiber phenotype expression from type IIb to IIa MHC was noted in EDL following cold exposure.…”
Section: Discussionsupporting
confidence: 68%
“…Suzuki et al [8] also reported that the soleus weight and the mean fiber cross-sectional area were significantly less in the cold-acclimated rats than in the control rats. The mean cross-sectional area of fibers expressing pure type I myosin heavy chain (MHC) of the same soleus muscle as in the current study was significantly less in the cold-exposed rats than in the control rats [24]. On the other hand, the weight of EDL relative to body weight was significantly increased after cold exposure.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Recently, we have reported that Korean sea diving women who have been diving throughout their lives in cold water have high capillarity (Bae et al. 2003) comparable to that in animals chronically immersed in cold water (Lee et al. 2004).…”
mentioning
confidence: 99%